Rural Family Caregivers' Discoveries Following a Person-in-Context Dementia Simulation - Candace Currie Harrington; Sonya R. Hardin; Pamela Z. Cacchione; Donna W. Roberson; Janice A. Neil (Rural Nurse Organization; Binghamton University, 2022)
Purpose: The purpose of this qualitative study was to discover rural family dementia caregivers' lived experience in a virtual dementia simulation and how it affected their understanding of their family members' daily challenges. To our knowledge, this study is the first to document its impact and value in this understudied, under-reported, and under-represented population. Sample: A volunteer sample of 10 rural family caregivers of persons with AD/ADRD following participation in a rural eastern North Carolina community delivered AD/ADRD simulation. Method: In-depth interviews lasting 45-110 minutes were conducted. The Utrecht phenomenology analytic method was used to sort, analyze, and interpret data. Richness of data drove the sample size. Results: The volunteer participants were female familial caregivers ages ranged from 49 to 81. Their care recipients' ages ranged from 62 to 93 years. Eighty percent of the caregivers provided care for their loved ones 6-7 days a week. Only one caregiver had formal (paid) assistance for care provision. The themes Now I Understand, Opened My Eyes, and Making Changes emerged from the participants' statements. Conclusion: Rural family caregivers found the AD/ADRD simulation profoundly impacted their perceptions of AD/ADRD and expressed new understandings and eye-opening epiphanies about their family members' daily challenges with dementia and their planned changes to improve their loved ones' quality of life.  The AD/ADRD simulated experience provided participants with a unique opportunity for self-discovery about their loved ones' daily challenges. This original study addresses the paucity of literature and research about AD/ADRD simulations for rural caregivers of persons with AD/ADRD. This study further demonstrates the value of AD/ADRD simulation to rural nursing practice and science. These findings may prompt rural health nurses to encourage family caregiver participation in person-in-context simulations to enhance their understanding of the loved ones' lived experience. Keywords: interpretative thematic analysis, dementia simulation, family caregiver, qualitative research, neurocognitive syndrome DOI: https://doi.org/10.14574/ojrnhc.v22i1.695